Photoalignment Studies on Azo Containing Thiophene Based Acrylates - Hegde, Gurumurthy; Alla, Rasha Ata; Asman, D. Chambers; M. M., Yusoff; Matharu, A. S.; Komitov, Lachezar (Trans Tech Publications, Switzerland, 2014)
The photoalignment properties of thin films made from several azo-containing thiophene-based acrylate with respect to the commercially available nematic liquid crystal (MLC 6873-100; Δε>o) is reported. As observed, the photoalignment ability of these films is influenced by the number and disposition of fluoro-substituents and the position of attachment of the terminal thiophene moiety. Inclusion of a lateral fluoro-substituent(s) provides excellent photo alignment ability whereas the non-fluorinated counterpart tends to give unsatisfactory alignment quality. The performed study showed also that 2-substituted thiophenes give better photoalignment quality.